2016
DOI: 10.1063/1.4944506
|View full text |Cite
|
Sign up to set email alerts
|

Structure and optical properties of aSiAl and aSiAlHx magnetron sputtered thin films

Abstract: Thin films of homogeneous mixture of amorphous silicon and aluminum were produced with magnetron sputtering using 2-phase Al–Si targets. The films exhibited variable compositions, with and without the presence of hydrogen, aSi1−xAlx and aSi1−xAlxHy. The structure and optical properties of the films were investigated using transmission electron microscopy, X-ray photoelectron spectroscopy, UV-VisNIR spectrometry, ellipsometry, and atomistic modeling. We studied the effect of alloying aSi with Al (within the ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…The reflectance during Al removal was modeled by using the transfer-matrix model and approximating the nanostructure to consist of several planar layers with different Al concentrations [28]. The effective refractive index for each layer has been estimated by using the Bruggeman effective medium approximation with a polarization factor of ½ for circular rods [29,30] and known refractive indexes for all components [31,32,33,34]. To estimate the volume fraction, we have assumed that as the Al is removed, half of the remaining elemental silicon is in the form of SiO 2 and that the expansion of the Si as it oxidizes reduces the void by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…The reflectance during Al removal was modeled by using the transfer-matrix model and approximating the nanostructure to consist of several planar layers with different Al concentrations [28]. The effective refractive index for each layer has been estimated by using the Bruggeman effective medium approximation with a polarization factor of ½ for circular rods [29,30] and known refractive indexes for all components [31,32,33,34]. To estimate the volume fraction, we have assumed that as the Al is removed, half of the remaining elemental silicon is in the form of SiO 2 and that the expansion of the Si as it oxidizes reduces the void by 50%.…”
Section: Resultsmentioning
confidence: 99%
“…So the optical transition of the polysilicon induced by layer exchange with aluminum in Al/Si annealed films undergoes indirectly. 41 , 46 Figure 10 shows Tauc’s plot of Al/Si films. The following Table 3 shows the values of optical energy gap of the prepared samples.…”
Section: Resultsmentioning
confidence: 99%
“…Or it can transfer to a direct transition by incorporation of Sn interstitially in polysilicon lattice as we discussed below. So the optical transition of the polysilicon induced by layer exchange with aluminum in Al/Si annealed films undergoes indirectly. , Figure shows Tauc’s plot of Al/Si films. The following Table shows the values of optical energy gap of the prepared samples.…”
Section: Resultsmentioning
confidence: 99%
“…In a previous work, we have shown that homogenous single phased aSi 1−x Al x (aSiAl) and aSi 1−x Al x H y (aSiAl:H) films can been made via magnetron sputtering [7]. Due to the low solubility of Al in Si, aSiAl alloys with high Al content have not been extensively investigated neither in a structural or an optoelectronic context.…”
Section: Introductionmentioning
confidence: 99%
“…There is therefore currently a lack of knowledge and understanding of the alloying mechanisms. Changing the stochiometry of our aSiAl and aSiAl:H films resulted in a change in band gap and di electric constant [7]. In this paper we want to relate the change in band gap and dielectric constant to the interatomic electron charge (re-)distribution between the constituent atoms of the amorphous alloys, namely Al, Si and H. The extent to which charge transfer takes place between atoms affects local electronic structure and determines the nature of their bonding.…”
Section: Introductionmentioning
confidence: 99%